'Nothing is simply one thing': Woolf, Deleuze and Difference. - Monaco, Beatrice (Deleuze Studies, 2013)
This paper explores some key texts of Virginia Woolf in the context of Deleuzian concepts. Using a close reading style, it shows how the prose poetry in Mrs Dalloway engages a complex interplay of repetition and difference, resulting in a remarkably similar model of the three syntheses of time as Deleuze understands them. It subsequently explores Woolf's technical processes in a key passage from To the Lighthouse, showing how the prose-poetic technique systematically undoes the structures of logical fact and rationality inscribed in both language and everyday speech to an extremely precise level.